SUPPLY INDUSTRY DYNAMICS FOR BRAZILIAN SUGARCANE - Amui, Lara Bartocci Liboni; Toledo Junior, Rudinei; Carrijo, Michelle de Castro; Cezarino, Luciana Oranges (Brazilian Journal of Operations & Production Management, 2015)
Sugarcane industry in Brazil is highly competitive in the production of ethanol, sugar and energy. This industrial competitiveness was also achieved through the development of the equipment involved in the production processes. The industry that supplies the equipment plays an important role in the competitiveness of sugarcane sector. This study seeks to analyze the organization and configuration of the equipment supply industries for sugar, ethanol and energy mills in Brazil. The study seeks to evaluate how innovation occurs in this sector, contributing to an important discussion about maintaining competitiveness and proposing a typology for this industry. The study is based on an analysis of information obtained through a set of interviews with leaders and entrepreneurs in the industry. The results allow us to conclude that the growing modernization of the sector will require greater efforts from the equipment industry to provide plants with necessary technological innovations and possible efficiency gains